A tropically adapted green and energy-efficient building how to create your own triple green sustainable house - Wagner, Karl (University of Malaya Press, 2017)
Roughly 65% of energy consumption in Malaysia comes from running cooling appliances. This book sets out how this can be changed by, surprisingly, altering and designing airtight houses with carefully controlled fresh air ventilation. The design is based on a similar one imported from Germany, but cleverly adapted to a tropical climate.